Implementasi Tadabbur Berbasis Maqāṣid Al-Qur’an - Senjaya, Sutisna; Kosasih, Aceng; Hermawan, Wawan; Oki, Alber (ZAD Al-Mufassirin, 2023)
The Qur'an is a ma'dubatullāh that must be enjoyed by human beings in order to achieve a sense of closeness to Him (rabbāniyyūn) through the excavation of the menu of faith, knowledge and act. This study was conducted with a qualitative approach based on a literature study, then the techniques are presented descriptively and analytically. The result is one of the alternative steps to do tadabbur Al-Qur’an based on maqāṣid Al-Qur’an with a syntax that consists of four stages: (1) al-qira’ah; reciting verse after verse according to the theme of the surah (mauḍū ’), (2) al-ta’ammul wa al-tafsīr; pay attention to the general purpose of the surah (maqāṣid al-sūrah) and understand the meaning (ma’na) of each verse based on several interpretations, (3) al-istikhrāj; issue the purposes of each verse (maqāṣid al-ayāt) and (4) al-isṭinbāt; draw conclusions from the purposes of each verse into the main purposes of the Qur’ān (maqāṣid Al-Qur’an). The application of tadabbur method has implications on the intensity of interaction with the Qur’ān and the achievement of Islamic educational goals.